2019
DOI: 10.1007/s10278-019-00215-1
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhancing Snapshot Narrow-Band Imaging Method for Real-Time Computer-Aided Cervical Cancer Screening

Abstract: Composition of cervical precancerous lesions and carcinoma in situ is rich in hemoglobin, unlike healthy tissues. In this study, we aimed to utilize this difference to enhance the contrast between healthy and diseased tissues via snapshot narrow-band imaging (SNBI). Four narrow-band images centered at wavelengths of characteristic absorption/reflection peaks of hemoglobin were captured with zero-time delay in between by a custom-designed SNBI video camera. Then these spectral images were fused in real time int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The results could be used to alert healthcare workers regarding the negative effects of COVID-19 on these tests and the need for greater caution in applying and interpreting these results. The importance of external evaluation of cervical cytology and computer system implementation has been addressed previously [ 28 , 29 ]. In addition, revision of current health care policies appears warranted to reverse the substantial damage that this pandemic has inflicted on health care programs, specifically those for the prevention of cervical cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results could be used to alert healthcare workers regarding the negative effects of COVID-19 on these tests and the need for greater caution in applying and interpreting these results. The importance of external evaluation of cervical cytology and computer system implementation has been addressed previously [ 28 , 29 ]. In addition, revision of current health care policies appears warranted to reverse the substantial damage that this pandemic has inflicted on health care programs, specifically those for the prevention of cervical cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of this technique is that it does not require external reagents to stain the cervix and diagnose cancer. 50 Kobara et al compared NBI with colposcopy in detecting CIN and CIN2+ lesions. The study showed that NBI is highly sensitive (87%) than colposcopy (74%) but has a low specificity (50%) when compared with that of colposcopy (68%).…”
Section: Narrow-band Imagingmentioning
confidence: 99%
“…8(b). The main advantage of this technique is that it does not require external reagents to stain the cervix and diagnose cancer 50 . Kobara et al.…”
Section: Optical Modalities For Cervical Cancer Detectionmentioning
confidence: 99%
“…Again, hyperspectral imaging-based approaches have many benefits, including the fact that they are non-invasive and may reduce the need for unnecessary biopsies. 5 However, the current spectrum imaging technique collects data by performing successive scanning in the spatial domain to cover the area that must be diagnosed. Therefore, collecting the necessary diagnosis data requires time because it takes time for current spectral or hyperspectral imaging techniques to scan the entire cervix.…”
Section: Introductionmentioning
confidence: 99%